The geodetic mass balance and ice thickness of Tungnafellsjökull ice cap - Ágúst Þór Gunnlaugsson 1987- (2016)
Tungnafellsjökull is a small ice-cap in the center of the Icelandic highlands. Little has been known about the long term evolution of the ice-cap during the last decades. To estimate the long term geodetic-balance of Tungnafellsjökull, the method of photogrammetry was used for creation of digital elevation models (DEMs) for the years 1960, 1986 and 1995. Additional DEMs from 2004, 2011 and 2013 were used for to estimate the surface changes of Tungnafellsjökull. In addition, radio echo sounding (RES) was used for measuring the thickness of the ice-cap. By comparing together DEMs that represents the glacier surface at different times, the surface elevation changes can be measured. The results indicate that the mass balance of the ice-cap was close to equilibrium for the period 1960 to 1995. From 1995 to 2013 the geodetic mass balance rate has been negative reaching -0.80 ± 0.39 m.w.e.y-1 for the period 1995 to 2004. The response of Tungnafellsjökull to atmospheric temperature change since 1995 is in coherence with the available data from other glaciers in Iceland and in the northern hemisphere for the same period. From 1960 to 2013 Tungnafellsjökull lost 20% of its volume, or from 2.66 ± 0.08 km3 in 1960 to 2.10 ± 0.01 km3 in 2013. The glacier area was reduced by ~ 16 % in the study period, from 37.56 ± 0.94 km2 in 1960 to 31.60 ± 0.79 km2 in 2013. Comparison with its neighboring glaciers indicate a stronger coherence with the mass balance of Köldukvíslarjökull outlet in NW-Vatnajökull rather than on Þjórsárjökull outlet in the eastern part of Hofsjökull. Tungnafellsjökull er lítill jökull (~ 32 km2) á hálendi Íslands en lítið er vitað um þróun þess jökuls undanfarna áratugi. Til að meta langtíma afkomu jökulsins var beitt aðferð sem ber saman hæðarlíkön sem útbúin eru út frá loftmyndum sem teknar voru árin 1960, 1986 og 1995. Að auki voru hæðarlíkön frá 2004, 2011 og 2013 nýtt til að meta yfirborðsbreytingar á jöklinum. Einnig voru framkvæmdar íssjármælingar vorið 2013 sem gáfu upplýsingar um heildar rúmmál ...